Requirements for the Development of Cardiovascular Stents and Features of Increasing Their Bioactivity (Texas Journal of Agriculture and Biological Sciences, 2022)
Cardiovascular disease today is one of the leading causes of death. The heart is a muscular organ that constantly pumps blood. Over time, the blood vessels thicken and form the inner shell. This inner coating causes great inconvenience in performing the function of blood vessels. As a result, coronary heart disease occurs. In addition to preventing these types of diseases, they can currently be eliminated only by surgically installing a stent in the vessels of the heart. Below is information on the requirements for the development of stents and their properties that increase biological activity.